2011
DOI: 10.1097/sla.0b013e31823003b5
|View full text |Cite
|
Sign up to set email alerts
|

Single Incision Versus Standard 3-Port Laparoscopic Appendectomy

Abstract: The single site umbilical laparoscopic approach to appendectomy produces longer operative times resulting in greater charges. However, these small differences are likely of marginal clinical relevance. The study was registered with clinicaltrials.gov at the inception of enrollment (NCT00981136).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
143
0
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 214 publications
(153 citation statements)
references
References 21 publications
6
143
0
2
Order By: Relevance
“…Although the remaining variables were comparable in both groups which was similar to our study. 11 Kang et al in another study concluded that other than a marginal increase in operative time in SILA (0.276) all the other variables were quite comparable. 12 The glove port technique although cost effective could considerably increase operative time as it has a steep learning curve, and surgeons require high technical skills to perform it.…”
Section: Discussionmentioning
confidence: 97%
“…Although the remaining variables were comparable in both groups which was similar to our study. 11 Kang et al in another study concluded that other than a marginal increase in operative time in SILA (0.276) all the other variables were quite comparable. 12 The glove port technique although cost effective could considerably increase operative time as it has a steep learning curve, and surgeons require high technical skills to perform it.…”
Section: Discussionmentioning
confidence: 97%
“…Other complications such as postoperative ileus or surgical wound infection, among others, showed no significant differences. Peters et al [37] stated that there was no significant difference in wound infection between the SPILA group (6/180) and the three-port group (3/180). A single patient suffered an intra-abdominal abscess, occurring in the three-port group.…”
Section: Complicationsmentioning
confidence: 99%
“…A very low mortality rate shown by previous studies of 0.05% and 0.3% for laparoscopic and conventional open appendectomy respectively indicate safety of both procedures especially in absence of complicated disease. 18 In our studies overall postoperative complication was 24.5% for open and 6.7%for laparoscopic procedure with most common reported complication of wound dehiscence and wound infection especially in patients who underwent open appendectomy. Wound infection was more commonly observed in patients who had complicated appendicitis.…”
mentioning
confidence: 96%